Evaluatating the application of surface and sub-surface trickle irrigation systems for planting active peas in sandy soil - Abou El Azem, A. M.; Nessrien S. Abdel Kareem; M. A.M. Moursy (2013)
The current study investigates two modern irrigation systems, (i.e. surface and sub-surface trickle irrigation systems). It was applied in Wadi EINatron Experimental Station, which represents the new lands condition and it was applied on active pea crop. Three different emitter's discharges equal to 2, 4 and 8 1/h and two irrigation systems were evaluated based on six indicators, (i.e. yield, water application, water consumption, water use efficiency, soil moisture and salt patterns). Both investigated systems were tested under two conditions (i.e. 100% and 50% of the net crop water requirements). The results indicated a privilege for using sub-surface trickle irrigation system (i.e. according to the different indicators). The sub-surface trickle irrigation system had higher yield, higher Water Use Efficiency, lower water application and water consumption compared to surface trickle irrigation when I 00% of the net crop water requirements and 4 1/h emitter discharge were used. Also, this system gave sufficient available water and best distribution of moisture in the root zone. It was thus recommended to use the above conditions, under sandy soil, to achieve the lowest water application, water consumption, highest crop yield and water use efficiency.
Includes references.
Summary in Arabic.
1
Keywords: Peas -- Irrigation; Microirrigation; irrigation systems